Institutions and administrative bodies, and their role in the processes of integration and disintegration in Silesia - Wąs, Gabriela (Publishing House eBooki.com.pl, 2014)
The Early Modern Period in formation of the political and social order is marked by the formation, in the beginning of said epoch, of distinct institutions and offices for the purpose of ruling Silesia, pan-Silesian, estate and ducal in various jurisdictions in Silesia, said system – with changes introduced in the absolute reign after 1629 – survived until 1740. Factors which influenced the perception of being separate among the social and political elite of Silesia were the institutions forming for the purpose of administrating the country in the time when links with the Bohemian Crown were weakened, especially in the latter part of the 15th and beginnings of the 16th century. This influenced the formation of Silesian institutions as having a great deal of autonomy in regards to the rule of the king and other institutions of the monarchy. The distinctly Silesian social structure was also influential in forming the distinctiveness of Silesian institutions. Formation of regions was also influenced by the institutional and political structure of the monarchy, which was comprised of five countries, all of which had their own estate representation, and comprised nearly all, available in those times, aspects of governing the society. The Thirty Years’ War became the caesura of Silesian regionalism: the monarchy managed to marginalise the Silesian political regionalism, although reforms after 1629 maintained the administrational and institutional regional system of Silesia.
Keywords: Silesia; regional history; regional administration; socio-political structure